WEB-BASED ONLINE PLATFORM: AN EDUCATIONAL HUB - Kumar, Abhishek; Kumar, Ankesh; Singh, Atul Kumar; Chauhan, Ishwar Chand; Singh, R K (International Journal of Research -GRANTHAALAYAH, 2025)
The aim of this study was to develop a study material system to serve as a secure, efficient, and reliable databank for notes documents of undergraduate. The system was designed to be user friendly and comply with the specified requirements. There is need to utilize the technology in the hands of everyone to implement learning. At present, humankind is facing rapid and profound changes in society, science, technology, economy and environment. The 21st century has witnessed extraordinary scientific and technological progressions. Improvement of technology has generated new educational technique known as e-learning. Nowadays, popularity of e-learning is growing rapidly and numerous educational organizations, public, academic and digital libraries are embracing it. Lately, engineering education is heading toward the blended education system as it successfully combines both chalk and talk system (face-to-face), computer-assisted learning methodologies and internet access feature to learners.